Contrast Hysterosonographic Evaluation of Niche Prevalence Following a Standardized Suturing Technique for Caesarean Sections - Hafner, Anita; Pohle, Marie Christine; Rauh, Maximilian; Schnabel, Annegret; Meyer, Sylvia; Köninger, Angela (Geburtshilfe und Frauenheilkunde, 2024)
After caesarean section a uterine niche can be detected in 42–84% of all women and in 11–45% large defects with a residual myometrium < 2.2 mm occur. If the niche compromises > 50% of myometrial thickness, risk of uterine rupture during birth increases. The suturing technique might contribute substantially on pathogenesis of niches. The objective of this study is to investigate the effect of the suturing technique on niche prevalence by using a standardized two-layer surgical technique.Women with one previous caesarean section were examined within 6–23 months after caesarean section using contrast medium-supported transvaginal sonography regarding the prevalence, sonomorphological aspect and clinical symptoms of a uterine niche. The surgical technique used was: dilatation of the cervix, interrupted suture of the first layer (excluding the endometrium), continuous closure of the visceral and parietal peritoneum.Using native vaginal sonography, no niches were visible in the whole cohort. In three cases, there was a small niche detectable with a depth between 2.3 and 3.9 mm by contrast hysterosonography. Regarding the total myometrial thickness, the niche depth compromised less than 50%. All patients were symptom-free.In our study population, there were only three cases (9.1%) with a small uterine niche. Residual myometrium and niche percentage on myometrial thickness were excellent in all three cases. Thus, our results show that the uterotomy closure technique used in the study cohort might be superior with respect to the development of uterine niches compared with the expected prevalence.
Keywords: uterine niche; caesarean scar defect; isthmocele; uterotomy closure technique; wound healing; contrast hysterosonography